(3GdGbJUGO GdSjGMj (B/s - (3YHhj, RjO efjQs ((3YeGf(B: s (3OGQ GdQGjI ddfTQ hGdJhRjY(B, s, 2008)
(3JYQja GdSjGMI hCgejJgG, GdSjGMI h YdGbJgG HYde GdGbJUGO, CgejI bWGY GdafObI HGdfSHI ddSjGMI h GdLOhi GdGbJUGOjI dgG, GdHjFI GdGbJUGOjI ddSjGMI, eSGgeI GdSjGMI h GdafObI aj GdfTGW GdGbJUGOj, Gdfeh GdGbJUGOj aj bWGY GdSjGMI h GdafObI, GdGgejI GdGbJUGOjI h YdGbJgG HGdJfhY GdHjhdhLj, GdGbJUGO GdSjGMj aj GdOhd GdYQHjI, GdGbJUGO GdSjGMj aj cd ef Ohd GdNdjL , ShQjG , eUQ , djHjG , GdLRGFQs
(3HHdjhZQGajG(B: (3U(B.247s
Keywords: (3GdLRGFQ(B-(3GdSjGMIs; (3GdSjGMI(B- (3GbJUGOjGJs; (3eUQ(B-(3GdSjGMIs